Enteral tube feeding: prevalence and nutritional status of neurosurgical patients from Hospital Sungai Buloh, Malaysia / Ahmad Aizat Abd. Ghani…[et al.] - Abd Ghani, Ahmad Aizat; Adnan, Muhamad Shahnizam; Khalid, Muhamad Shukry; Juhari, Nabhan Nazif (2015)
Enteral tube feeding (ETF) is a crucial step in order to improve the nutritional status of critically ill patients. Thus, feeding practices among health care practitioners would affect largely to the fate of the hospitalized patients. There were some of consequences if the ETF was not practiced accordingly such as malnutrition, increased length of stay and worsen complications. For that causes, this study would investigate the prevalence, feeding practices, anthropometry, biochemical profiles, energy adequacy and the length of stay among the neurosurgery patients at Hospital Sungai Buloh. The feeding practices include route of administration, mode of administration, types of formula and frequency of changing tube. Whereas, the anthropometry value would comprise height, weight, body mass index (BMI) triceps skinfold (TSF), mid-arm circumference (MAC) and mid arm muscle area (MAMA). This study used an experimental cross-sectional and descriptive study design which include filling the data collection form by using the information gathered from medical records, anthropometry measurement and the input/output chart written by nurses. The subjects were examined within 48 hours upon admitted to the ward (tO) as baseline and were followed up two weeks later (tl). The prevalence of patients admitted to neurosurgery ward with enteral tube feeding (ETF) was 44 patients (10.9%). In term of formula selection, 66% patients had received polymeric formula, 17% on specialized formula where the remaining 17% of the patients received combination of formulas. Mean BMI was decreased from baseline by 1.3 kg/m2. The difference of mean BMI between tO and tl was statistically significant, (p value = 0.01). While, the mean MAMA was decreased by 3.1 cm2. The difference of mean MAMA between tO and tl was also significant, (p value = 0.041). For the biochemical results, by using Pearson's Chi-Square test, only creatinine had shown a significant association with MAMA at tl, (p value = 0.005). By using the Pearson's Chi-Square test, energy adequacy had also shown a significant association of with MAMA at tl, (p value = 0.019). The mean length of stay for the discharged patients within the data collection period was 26 days for 13 patients. In conclusion, this study is important for development of suitable intervention for malnutrition among hospitalized patients. This would also increase the awareness of the health care providers about the importance of feeding practices of ETF.